Consistent Forecasting in a Dynamic Multi-Sector Model - Almon, Clopper (The Review of Economics and Statistics, 1963)
T HE basic idea of consistent forecasting is very simple: make forecasts of the output of each industry, the wage rate, and perhaps other variables in such a way that, if business acts on the basis of the forecasts, they will come true and full employment will be obtained. The idea is not new, but the possibilities of putting it to work in the American economy have not been developed. I believe that these possibilities are considerable and hope that this paper can be a first step in making from them an effective tool for assisting a free economy to maintain steady growth and full employment. The forecasts yielded by a model like the present one would be intended to guide capital investment planning by business. Short-term movements will be given scant attention here. Section I explains the theory of the model. Since the version presented here is only a first step toward consistent forecasting of practical use for business planning, it seemed advisable to keep it as simple as possible and then, by numerical work, compare its functioning with the actual performance of the American economy. In this way, its greatest needs for extension and refinement can be brought to light and used as guides for future work. The model becomes the Leontief open dynamic system if it is known that full employment can be maintained with a of a constant wage rate. A method of getting the economically relevant solution to this special case is developed and then extended to the variable wage rate case. The last paragraph of the section discusses how consistent forecasting could fit into a free economy. In Section II, a ten-sector model of the American economy is used to forecast from I953 to I960, with only the course of the total labor force and the exogenous final demandsexports, government, and capital replacement known in advance. A comparison of the results with the actual course of events indicates that increasing productivity of new capital and a limited amount of variation of input coefficients must be included before practical forecasting can be done. At the same time, however, the comparison suggests that even the simple model is getting at something very relevant to the economy and that, after taking account of the suggested improvements, a useful tool can be obtained. The comparison also offers, as a sort of by-product, a surprisingly clear-cut explanation of the I954 and I958 recessions. But the result of the comparison which I would like for the reader to bear in mind, particularly when considering business acceptance of the forecasts, is that they are quite sensible looking and businesslike.